Research and application of nozzles with inclined inlet channels for jet sulphitators in the sugar industry - Ponomarenko, Vitaliy; Liulka, Dmytro; Vasyliv, Volodymyr; Yakobchuk, Roman; Babko, Evhen; Slyva, Yuliia (My University, 2024)
The paper was devoted to the study of the process of liquid spraying by nozzles used in jet sulphitators in the sugar industry or as separate equipment. Liquid sprayers play a major role in ensuring efficient operation of heat and mass transfer equipment due to the creation of a significant contact surface. When designing or auditing its technical integrity, it is necessary to have reliable hydrodynamic characteristics of sprayers. Research in this area is relevant. The purpose of the study was to establish all the characteristics of liquid flow in the elements of the nozzle and spray swath using comprehensive research (experimental and computer) for the possibility of intensifying the operation of equipment, in particular, sulphitators for the sugar industry. To achieve this goal, experimental (studies of injectors and ejectors on a hydraulic stand) and CFD studies of these objects in the modules of the ANSYS software suite (version: ANSYS 2020 R2) were conducted. The dependence of the nozzle flow rate on the liquid pressure and the number of supply channels for different types of injectors (jet, centrifugal-jet) has been experimentally established. It has been experimentally confirmed that the uniformity of liquid distribution in the nozzle swath with two supply channels was high and sufficient for practical applications. In the CFD study of the characteristics of the nozzle spray swath, it was proposed to reduce the design area to the cut cone, which reduced the calculation time. When modelling the hydrodynamics of the liquid in the nozzle, numerically characteristic velocities were determined both in the nozzle elements and in the outlet. It was established that there was a vacuum in the root zone reaching 865 Pa for this nozzle at a liquid inlet pressure of 0.25 MPa, which led to gas ejection into the swath. The above calculation methodology was relevant for determining the characteristics of injectors, in the development and design of new sprayers with a given capacity and a spray swath, used both as active ejector nozzles and as independent equipment for dispersing process liquids in the food industry
Keywords: кафедра технологічного обладнання та комп’ютерних технологій проектування; сульфітатор струменевий; форсунка розпилювальна; jet sulfitator; spray nozzle; CFD modeling